Luminescence and physical properties of Ce3+-doped potassium gadolinium phosphate glasses for radiation detector application. (August 2021) - Yodkantee, D.; Prasatkhetragarn, A.; Chanthima, N.; Tariwong, Y.; Kothan, S.; Rujirawat, S.; Yimnirun, R.; Kidkhunthod, P.; Kim, H.J.; Limsuwan, P.; Kaewkhao, J.
Abstract: This work aimed to study the effect of Gd2 O3 and CeF3 modified on potassium gadolinium phosphate glasses scintillators in 17K2 O: xGd2 O3 : (82.5-x)P2 O5 : 0.5CeF3 (where x = 9, 11, 13, 15 and 17 mol%) and 17K2 O: 17Gd2 O3 : (66-x)P2 O5 : xCeF3 (where x = 0.1, 0.3, 1, 1.5, 2, 3 and 5 mol%) systems produced by the melt quenching technique. The physical, optical, and scintillation properties of the specimens were measured and discussed. The density and molar volume of the glasses trend to increases with increasing Gd2 O3 concentration, while an invariable for all CeF3 concentration. The photoluminescence and x-ray luminescence spectrums show the highest value at 9 and 17 mol% of Gd2 O3 concentration, respectively, which shows the decay time between 15.02 and 22.84 ns. XANES results shows the main oxidation state of Ce is 3+ ion for all glasses. However, the photoluminescence and x-ray luminescence spectrums show the maximum value at 5 mol% of CeF3 concentration, which shows the fast decay time between 16.26 and 36.02 ns. These results of the x-ray induced luminescence and the fast decay time in nanoseconds level are possible applied as well as the scintillation materials for radiation detector application. Highlights: Gd 3+ and Ce 3 doped phosphate glasses were investigated. PL result shows energy transfer from Gd 3+ to Ce 3 . X-ray luminescence highest value at 17 mol% of Gd2 O3 and 5 mol% of CeF3 . Nanoseconds decay time are observed and may use as scintillator.